2015
DOI: 10.1016/j.ibusrev.2014.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Good corporate governance in Nigeria: Antecedents, propositions and peculiarities

Abstract: The full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.Please consult the full DRO policy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
94
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(97 citation statements)
references
References 97 publications
1
94
0
2
Order By: Relevance
“…As such we attempt to answer the question: why and how might local firms pursue CSR practices in weak institutional contexts? Our enquiry is guided by the extant literature on the institutional theorising of CSR in varieties of capitalism and the literature on responsible business practices in developing economies (Idemudia and Ite, 2006;Eweje, 2006;Azmat and Samaratunge, 2009;Amaeshi et al, 2006;Adegbite et al, , 2013Adegbite, 2014;Blowfield and Frynas, 2005;Campbell, 2007;Deakin and Whittaker, 2007;McWilliams and Siegel, 2001;Aguilera et.al. 2006Aguilera et.al.…”
Section: Figure 1: Institutional Conditions For Csrmentioning
confidence: 99%
“…As such we attempt to answer the question: why and how might local firms pursue CSR practices in weak institutional contexts? Our enquiry is guided by the extant literature on the institutional theorising of CSR in varieties of capitalism and the literature on responsible business practices in developing economies (Idemudia and Ite, 2006;Eweje, 2006;Azmat and Samaratunge, 2009;Amaeshi et al, 2006;Adegbite et al, , 2013Adegbite, 2014;Blowfield and Frynas, 2005;Campbell, 2007;Deakin and Whittaker, 2007;McWilliams and Siegel, 2001;Aguilera et.al. 2006Aguilera et.al.…”
Section: Figure 1: Institutional Conditions For Csrmentioning
confidence: 99%
“…A review of qualitative studies (see, for instance, Adegbite, 2015;Nakpodia et al, 2016) Flick (2014) informed that in an interview-based study, it is important to decide whom to interview, and from which group. As this study focused on the connection between religion and corporate governance practices in Nigeria, a considerable number of interviewees (corporate executives) came from companies listed on the Nigerian Stock Exchange (NSE) (the foremost stock exchange in Nigeria).…”
Section: Methodsmentioning
confidence: 99%
“…Nonetheless, Adegbite (2015) suggested that elites, including those in religious environments, trigger corruption in Nigeria.…”
Section: Systemic Corruptionmentioning
confidence: 99%
“…Although, there are studies in this area from some emerging economies however, the corporate governance landscape in countries varies hence, limiting the generalizability of the frequently researched Anglo-American system in the Nigeria setting. In the sense that the indigenization policy embarked upon by the Nigerian government as some point in time lead to majority share ownership mostly held by founding families who have significant influence on board and on management [13]. Accordingly, the assumptions of market efficiency, competitive market and market mechanisms which agency theory presuppose are not validly applicable in the Nigerian where ownership concentrated [13].…”
Section: Introductionmentioning
confidence: 99%
“…In the sense that the indigenization policy embarked upon by the Nigerian government as some point in time lead to majority share ownership mostly held by founding families who have significant influence on board and on management [13]. Accordingly, the assumptions of market efficiency, competitive market and market mechanisms which agency theory presuppose are not validly applicable in the Nigerian where ownership concentrated [13]. Moreover, the code of corporate governance that was revised in 2011 just codified the requirement for the inclusion of non-executive independent directors and some companies are yet to comply with this requirement.…”
Section: Introductionmentioning
confidence: 99%